Integration and acceptability of cervical cancer screening as part of postnatal care among women attending postnatal clinics in the Accra Metropolis, Greater Accra Region, Ghana. - Lawrence Oppong Buadi; Raphael Odame; Ali Samba; Mumuni Kareem; Angela Amoanimaa Boateng; Claudette Ahliba Diogo; Rebecca Tricia Morrision; George Kumi Kwakye; Cecilia Smith-Togobo (PLOS Global Public Health)
Cervical cancer is a recognized preventable disease yet the fourth most common cancer among women globally. This study assessed the integration and acceptability of cervical cancer screening as part of routine sixth-week postnatal care among women attending a postnatal clinic. This was a cross-sectional descriptive study among 347 postpartum women who were attending their 6th-week postnatal visit. A Pap smear test was performed on each consenting study participant. Only conventional cervical smears were performed. The Pap smear samples were taken using a special kit (PAP-PAK Cytology brush kit) for a 3-smear sampling of the ectocervix (emphasis on the squamo-columnar junction), endocervix (endocervical canal past squamo-columnar junction) and the posterior fornix via a cervical-vaginal scraper and a CytoSoft cytology brush respectively. All smears were fixed with 95% ethyl alcohol and allowed to dry in cool air. The samples were sent to the cytology laboratory and stained with the Pap staining technique. All the smears were examined and reported by the cytology department of Korle-Bu Teaching Hospital. Descriptive statistics such as frequency tables were drawn and proportions were estimated. Bivariable analysis between categorical variables and outcome variables was done. A p-value ≤ 0.05 was considered statistically significant. Most (90.5%) of the study participants were satisfied with the Pap test procedure and about 52.7% indicated that paying Gh₵60.00 ($12.50) for screening test was affordable. The outcome of Pap smear tests revealed that most (90.8%) of the participants had normal Pap test results. In the univariable analysis, participants' educational level (p = 0.006); occupation (p < 0.001), and contraceptive use (p = 0.019) were significantly associated with the acceptability of the Pap test procedure. The multivariable analysis revealed that educational level (aOR = 3.27; 95% CI = 1.05-10.21; p = 0.041) and occupation (aOR = 6.49; 95% CI = 1.67-25.29; p = 0.007) were significantly associated with the acceptability of the Pap test procedure and showed higher odds of acceptability. Integration of cervical cancer screening into the routine sixth-week postnatal clinic has the potential to be feasible with anticipated high uptake. We therefore recommend a pilot study be initiated to integrate cervical cancer screening into the routine maternal health services as part of postnatal care. Also, the Ministry of Health/Ghana Health Service should initiate discussion with the National Health Insurance Authority for possible inclusion as part of the national health insurance scheme's benefit package in the nearby future.